Numerical Modeling of Historical Storm Tides and Waves and Their Interactions Along the U.S. East and Gulf Coasts. Issue 5 (26th May 2018) - Marsooli, Reza; Lin, Ning
Abstract: We apply a coupled circulation‐wave model to simulate extreme sea levels induced by tropical cyclones at the basin scale. We quantify storm tides, surges, waves, and their interactions for historical tropical cyclones (1988–2015) in the western North Atlantic Ocean. Comparisons between model results and field observations along the U.S. East and Gulf Coasts indicate that the overall performance of the model is satisfactory, with a root‐mean‐square error, bias, and Willmott skill of, respectively, 0.31, −0.04 m, and 0.9 for storm tides and 1.94 m, −0.22 m, and 0.87 for significant wave heights. Model results show that the highest surge levels were generated in Western Long Island Sound and NY/NJ Harbor, along the coasts of the Carolinas and Southwest Florida, near the Mississippi River delta, and along the coasts of Louisiana and East Texas. We find that the nonlinear tide‐surge interaction is often significant, but its contribution to peak storm tides induced by the most extreme events (i.e., storms that caused storm tides larger than 2 m) was moderate (−12% to 5%). We find that the maximum wave setup was relatively large (tens of cm) in most coastal regions, but it did not necessarily coincide with the peak storm tide. The contribution of wave setup to peak storm tides induced by the most extreme events was less than 17%. Finally, we show that while some offshore storms did not affect the coastal areas with high storm surges or strong winds, they generated the largest historical wave setup at the coast. Key Points: We build and validate a basin‐scale numerical model to simulate tides, and storm surges and waves induced by tropical cyclones We present spatial distributions of the highest historical water levels, storm surges, and waves along the U.S. East and Gulf Coasts The influence of tide‐surge interaction and wave setup on the water level can be relatively large in some coastal regions